Mencintai Karena Allah dalam Perspektif Hadits: Kajian Studi Tematik Hadits - Putri Nur Rahmawati; Zahra Khairunnisa; David Shubhi; Mus' idul Millah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
. In today's increasingly complex and diverse modern society, it is improtant to understand the role and meaning of love for god in the context of social, cultural, and everyday life. This study aims to discuss love for Allah in the perspective of hadith. This research uses a qualitative approach by applying the tematic method of hadith. The object of discussion in this study is the ethics and virtue of loving because of Allah which has been formulated based on the theme of hadith. The results. of research on this theme prove that the theme of hadith can be formulated within the framework of the theory of loving because of Allah in the perspective of hadith. In the discussion section, the researcher explains how the ethics of loving because of Allah and the virtue of loving because Allah of Allah take the essence of the sarah of the hadith. The conclusion of this study is that people who love everything because Allah yull get a great reward from Allah on the day of judgment and make a cause for getting.